The concentration-independence cellular effects of fibronectin adsorbed on material surfaces with different hydrophobicities - Le, Huong; Mai-Thi, Hoang-Nghi; Le, Xuan; Tran, Ngoc Quyen; Tu Tran, Cam; Huynh, Khon (Vietnam Journal of Biotechnology, 2022)
In tissue engineering, coating biomaterial’s surface with extracellular matrix (ECM) proteins can promote many biological activities, including cellular responses, wound healing, and rejection reduction. Several interactions occur upon binding proteins onto the surfaces, leading to changes in the protein structural conformation, directly affecting the cell-host interactions. Therefore, this study investigates the impacts of surfaces’ wettability on protein conformation. In order to get the insights, organosilicate (OGS) was utilized to modify the tissue culture plate, resulting in surfaces with different wettability, followed by fibronectin (FN) immobilization. Then, the surfaces were used to study the fibrinogen interaction, cell attachment, and spreading. The results showed that OGS-modified surfaces produced four different wettability, ranging from super-hydrophilic (OGS150), hydrophilic (OGS100), hydrophobic (OGS60), to super-hydrophobic (OGS5). Each surface possessed particular nature, resulting in the variation of FN molecules’ structural change. The amount of FN adsorbed on the OGS-coated surfaces was shown not to be perfectly proportional to the results of fibrinogen interaction, cell attachment, and spreading. The super-hydrophobic surfaces (OGS5) were highest in the amount of immobilized FN and the efficiency in subsequent experiments among the OGS-coated surfaces group. Notably, the hydrophobic surface adsorbed the lowest amount of FN but achieved remarkable results in the following experiments. Thus, this study holds a promising potential in producing biocompatible materials in tissue engineering.